Insula and putamen centered functional connectivity networks reflect healthy agers' subjective experience of cognitive fatigue in multiple tasks. (October 2019) - Anderson, Andrew J.; Ren, Ping; Baran, Timothy M.; Zhang, Zhengwu; Lin, Feng
Abstract: Cognitive fatigue (CF) impairs ability to perform daily activities, is a common complaint of aging and a symptom of multiple neurological conditions. However, knowledge of the neural basis of CF is limited. This is partially because CF is difficult to systematically modulate in brain imaging experiments. The most common approach has been to scan brain activity during effortful cognitive tasks. Consequently, neural correlates of CF tend to be task-specific and may vary across tasks. This makes it difficult to know how results generalize across studies and is outside the subjective experience of CF which tends to be similar in different tasks. It has been hypothesized that the subjective experience of CF might arise from domain general systems monitoring and acting on energy depletion in task specific circuits. Direct supporting neural evidence is lacking. By repeatedly scanning aging individuals undertaking four different tasks using functional Magnetic Resonance Imaging and referencing scans to detailed CF self-ratings taken before and after scanning, we sought task-general correlates of CF. We ran a data-driven representational similarity analysis, treating each brain region as a candidate CF functional connectivity hub, and correlating inter-participant differences in hub-based connectivity patterns with inter-participant differences in self-rated CF-profiles (a pattern of ratings across 18 questions). Both right insula and right putamen-based network connectivity patterns reflected CF across all tasks and could underpin subjective experience of CF.